The Effectiveness of Pruning and Atonic in Improving the Reproductive Development of Coffee Plants - Ni Luh Putu Sulis Dewi Damayanti; I Gusti Bagus Udayana; Yohanes Parlindungan Situmeang; Ni Kadek Desy Andya Dewi (Warmadewa University Press, 2026)
Decline in Arabica coffee productivity in the Kintamani highlands indicates agronomic constraints affecting the plant's reproductive phase. Pruning and the application of growth regulators are two essential approaches to improving the physiological balance that supports flower and fruit formation. This study aims to assess the effectiveness of pruning and Atonik application in promoting shoot, leaf, flower, and fruit-bud growth in Arabica coffee plants. The study was conducted over 12 weeks using a factorial design with a combination of pruning treatments and several Atonik dosage levels. Data were analysed using ANOVA and follow-up tests to determine the differences between treatments. The results showed that pruning consistently increased shoot regeneration and improved canopy structure, thereby optimising light capture efficiency and photosynthetic product distribution. The Atonik application strengthened the plants' physiological response by increasing meristem activity and nutrient absorption. The combination of both treatments produced the highest number of flowers and fruit buds compared to either treatment alone. Scientifically, these findings indicate that the enhancement of the generative phase is highly dependent on vegetative conditions, which are strengthened by canopy management and hormonal stimulation. This study makes an essential contribution to the development of coffee cultivation strategies that integrate pruning practices and hormone regulation to sustainably increase productivity.